Entrepreneurial activity and economic growth: A multi-country analysis - Manuel Almodóvar-González; Antonio Fernández-Portillo; Juan Carlos Díaz-Casero (European Research on Management and Business Economics (ERMBE), 2020)
Most scientific literature assumes that entrepreneurial activity, in a broad sense, is positive for economic growth. Our work analyses 74 economies in a period of 6 years, identifying those factors related simultaneously with an entrepreneurial spirit and economic growth. The results enable to know the impact of a specific factor on entrepreneurship and economic growth. Additionally, we suggest that entrepreneurial activity plays a different role depending on the economic stage of the country in question. On the other hand, less developed countries should not be based on generic entrepreneurship if the objective they pursue is to promote economic growth.
Keywords: O01; O04; L26; 650; Entrepreneurial activity; Entrepreneurship; Economic growth; Developing countries; Developed countries